Understanding the intention to use self service technologies in the airline industry. (16th July 2019) - Thamaraiselvan, N.; Arul, S. Thanigai; Kasilingam, Dharun
Self service technologies (SST) in the airline industry are becoming more common nowadays in the developing countries. This research seeks to understand the factors that affect the travellers' intention to use such technologies. Literature reveals that tech readiness, perceived ease of use and perceived reliability (PR) towards technologies play a role in the intention to use them. In order to test the hypotheses, data was collected from 552 travellers at Chennai Airport. Structural equation modelling (SEM) was used to test the hypotheses. Results indicate that perceived reliability and tech readiness are significant predictors of the intention to use SSTs. Managerial and theoretical implications are discussed.